Causal ascription of rework in building and civil engineering projects - Ekambaram, P.; Love, Peter; Kumaraswamy, M.; Ng, T. (Emerald Group Publishing Limited, 2014)
Purpose – Rework is an endemic problem in construction projects and has been identified as beinga significant factor contributing cost and schedule overruns. Causal ascription is necessary to obtainknowledge about the underlying nature of rework so that appropriate prevention mechanisms can be put in place. The paper aims to discuss these issues. Design/methodology/approach – Using a supervised questionnaire survey and case-study interviews, data from 112 building and engineering projects about the sources and causes of rework in projects were obtained. A multivariate exploration was conducted to examine the underlying relationships between rework variables.Findings – The analysis revealed that there was a significant difference between rework causes forbuilding and civil engineering projects. The set of associations explored in the analyses will be usefulto develop a generic causal model to examine the quantitative impact of rework on project performance so that appropriate prevention strategies can be identified and developed.Research limitations/implications – The limitations include: small data set (112 projects), whichinclude 75 from building and 37 from civil engineering projects. Practical implications – Meaningful insights into the rework occurrences in construction projects will pave pathways for rational mitigation and effective management measures. Originality/value – To date there has been limited empirical research that has sought to determine the causal ascription of rework, particularly in Hong Kong.